The Influence of Entrepreneurial Skills, Business Experience, and Social Media Support on Entrepreneurial Success in Medan City - Ryan, T. M. Adry (Smart International Management Journal, 2025)
This study examines how entrepreneurial abilities, accumulated business experience, and social media support influence business success among entrepreneurs in Medan City. Unlike previous research that examined these factors separately, this study integrates internal competencies and digital support within a local Indonesian context. A quantitative approach with descriptive and explanatory designs was applied to a population of 55 entrepreneurs using saturated sampling. Data were analyzed using multiple regression and path analysis. Results show that entrepreneurial skills (β = 0.412; t = 4.375; p < 0.001), business experience (β = 0.276; t = 3.040; p = 0.004), and social media support (β = 0.389; t = 4.145; p < 0.001) each positively and significantly affect entrepreneurial success. Collectively, the variables also have a significant effect (F = 53.873; p < 0.001), explaining 76% of the variance (R² = 0.760). These findings underscore the importance of enhancing entrepreneurial skills, practical experience, and digital engagement to achieve sustainable business success.